2020
DOI: 10.1080/14659891.2020.1736663
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the determinants of hookah smoking cessation among southern Iranian women: a qualitative study

Abstract: Background: Hookah smoking has been increasingly popular in Iran within the last two decades. The present study aims to explain the determinants of hookah smoking cessation among southern Iranian women in Bandar Abbas. Methods: The present study is a pioneering qualitative research that employed a conventional content analysis to explore factors affecting the hookah smoking cessation between 2018 and 2019. In total, 36 in-depth, semi-structured interviews were held with experienced individuals (15 women with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Further, having a strong influence from smoking friends; thinking that smoking makes the mind more relaxed; smoking makes the person appear as more grown up and independent from parents; and smoking helps people to forget their problems [9][10][11] . On the other hand, some of the perceptions that are commonly known in the literature about factors that encourage smoking cessation include: bans on indoor smoking; restricting advertising and selling of tobacco; support of family and friends; and spiritual support [12][13][14] . To date, there has not been a study conducted in Fiji on factors contributing to smoking initiation and cessation, therefore this study aimed to explore the reasons for adults becoming smokers and the factors affecting smoking initiation and cessation in Suva, Fiji.…”
Section: Introductionmentioning
confidence: 99%
“…Further, having a strong influence from smoking friends; thinking that smoking makes the mind more relaxed; smoking makes the person appear as more grown up and independent from parents; and smoking helps people to forget their problems [9][10][11] . On the other hand, some of the perceptions that are commonly known in the literature about factors that encourage smoking cessation include: bans on indoor smoking; restricting advertising and selling of tobacco; support of family and friends; and spiritual support [12][13][14] . To date, there has not been a study conducted in Fiji on factors contributing to smoking initiation and cessation, therefore this study aimed to explore the reasons for adults becoming smokers and the factors affecting smoking initiation and cessation in Suva, Fiji.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). In the first step, the results of a systematic review and two local qualitative studies, previously done and published elsewhere [ 29 – 31 ], were used to better understand the behavioral and environmental factors associated with HTS among women. The details of the other steps can be found in the published research protocol [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among these factors are positive attitude, underestimation of the hazards of HS, psychological and social gaps, physical and mental attachment to hookahs, family-related factors, media advertisement, ease of access (availability) and the absence of probative rules and poor monitoring and management [7,9,10]. In some other research, family support, social and psychological needs, family norms, control of external stimuli and political factors were among effective factors in hookah cessation [11]. In their study in the east Mediterranean region, A et al showed that socio-cultural norms, sensory characteristics of HS, motivation to smoke, gender differences, comparative effects of hookah and cigarette smoking and indicators of dependence/consumerism metaphors were among the determinants of HS [12] .…”
Section: Introductionmentioning
confidence: 94%